Metabolic adaptations of Shewanella eurypsychrophilus YLB-09 for survival in the high-pressure environment of the deep sea - Qiu, Xu; Tang, Xixiang (Frontiers in Microbiology, 2024)
Elucidation of the adaptation mechanisms and survival strategies of deep-sea microorganisms to extreme environments could provide a theoretical basis for the industrial development of extreme enzymes. There is currently a lack of understanding of the metabolic adaptation mechanisms of deep-sea microorganisms to high-pressure environments. The objective of this study was to investigate the metabolic regulatory mechanisms enabling a strain of the deep-sea bacterium Shewanella eurypsychrophilus to thrive under high-pressure conditions. To achieve this, we used nuclear magnetic resonance-based metabolomic and RNA sequencing-based transcriptomic analyses of S. eurypsychrophilus strain YLB-09, which was previously isolated by our research group and shown to be capable of tolerating high pressure levels and low temperatures.We found that high-pressure conditions had pronounced impacts on the metabolic pattern of YLB-09, as evidenced by alterations in energy, amino acid, and glycerolipid metabolism, among other processes. YLB-09 adapted to the high-pressure conditions of the deep sea by switching from aerobic intracellular energy metabolism to trimethylamine N-oxide respiration, altering the amino acid profile, and regulating the composition and the fluidity of cell membrane. The findings of our study demonstrate the capacity of microorganisms to alter their metabolism in response to elevated pressure, thereby establishing a foundation for a more profound understanding of the survival mechanisms of life in high-pressure environments.